WATER-SOLUBLE COMPLEX OF GOSSYPOL: PRODUCTION, STRUCTURE AND BIOLOGICAL ACTIVITY - Rezhepov, Kuralbay Zhadigerovich; Alimbaeva, Shiyrin Bekniyaz kizi (Химия растительного сырья, 2025)
The article provides information on the preparation and study of the structural and biological properties of water-soluble complexes of gossypol with N-polyvinylpyrrolidone. The most suitable method for obtaining complexes of N-polyvinylpyrrolidone with gossypol derivatives turned out to be a method that represents the co-precipitation of the starting gossypol with a polymer in non-aqueous solvent systems with stirring. In this way, a water-soluble complex of gossypol with N-polyvinylpyrrolidone was obtained. The resulting complex is a brightly colored powdery substance, completely soluble in water. Its physicochemical parameters are characterized. The structure of the resulting complex was confirmed by spectroscopy (UV, IR). In the course of the work, the relaxing effect of the PGN-02 polyphenol on the preparation of rat aorta was studied for the first time. Biological studies have shown that polyphenol PGN-02 has a strong relaxing effect and significantly reduces the force of contraction of the aorta caused by KCl (50 mM). It was shown that as a result of blocking the voltage-dependent L-type Ca2+ channels located in the plasmalemma, muscle relaxation occurred. The relaxing effect of PGN-02 polyphenol is associated with the blocking of L-type Ca2+ channels, as evidenced by the results of experiments conducted with the specific Ca2+ channel blocker verapamil.